2020
DOI: 10.4049/jimmunol.2000040
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses and Gut Microbiomes Distinguish HIV-Exposed from HIV-Unexposed Children in a Population-Specific Manner

Abstract: In both high-and low-income countries, HIV-negative children born to HIV-positive mothers (HIV exposed, uninfected [HEU]) are more susceptible to severe infection than HIV-unexposed, uninfected (HUU) children, with altered innate immunity hypothesized to be a cause. Both the gut microbiome and systemic innate immunity differ across biogeographically distinct settings, and the two are known to influence each other. And although the gut microbiome is influenced by HIV infection and may contribute to altered immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We found only two other studies in the literature that compared the gut microbiomes in HEU and HUU. Although each study enrolled only 9 to 25 children/group at around 2 years of age, they found similar alpha and beta diversity in the two groups, supporting our results ( 63 , 64 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found only two other studies in the literature that compared the gut microbiomes in HEU and HUU. Although each study enrolled only 9 to 25 children/group at around 2 years of age, they found similar alpha and beta diversity in the two groups, supporting our results ( 63 , 64 ).…”
Section: Discussionsupporting
confidence: 87%
“…Subsequently, D’Souza et al compared the structure of the gut microbiome at 6, 16, and 24 weeks of age in HEU receiving co-trimoxazole prophylaxis or not and showed that co-trimoxazole administration may also contribute to the dysbiosis observed in HEU ( 62 ). Two other cross-sectional studies that compared HEU and HUU gut microbiomes at approximately 2 years of life found similar alpha or beta diversities in the two groups ( 63 , 64 ).…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, HEU infants display high morbidity and mortality from pneumonia, diarrheal disease and sepsis [13,14] as well as poor growth and neurodevelopment [15]. The underlying reasons for such clinical differences are most likely multifactorial and dependent on the geographical and social setting, maternal health status and breastfeeding [16][17][18][19]. Of note, recent data have demonstrated that maternal HIV infection is linked to modifications in the fecal microbiome of HEU with alterations in the abundance of several taxa and functional profiles, suggesting that gut dysbiosis may contribute to the clinical vulnerability in this setting [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…CHEU also receive prophylactic antibiotics, to prevent infectious morbidity associated with HIV exposure. Each of these exposures may influence the seeding and succession of the gut microbiome in CHEU (28, 29), which may contribute to the high prevalence of stunting observed in CHEU (30). Evidence of the effect of other early-life environmental exposures on the assembly of the infant gut microbiome in low resources settings is scarce but may provide insights into the influence of microbial and microbiota-modifying exposures on child growth in the context of undernutrition.…”
Section: Introductionmentioning
confidence: 99%